Creative project management : innovative project options to solve problems on time and under budget - Dobson, Michael S.; Leeman, Ted (McGraw Hill, 2010)
Presents the seven essential tools for keeping projects on time and under budget. This book combines traditional project management skills, such as risk evaluation, decision-making, and human dynamics, with outside-the-box thinking and business creativity